2002
DOI: 10.1111/j.1582-4934.2002.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of angiogenic response by ischemic and hypoxic reconditioning of the heart

Abstract: This review is intended to discuss the newly discovered role of preconditioning which should make it an attractive therapeutic stimulus for repairing the injured myocardium. We recently found that apart from rendering the myocardium tolerant to ischemic reperfusion injury, preconditioning also potentiates angiogenesis. Our study demonstrated for the first time that both ischemic and hypoxic preconditioning triggered myocardial angiogenesis at the capillary and arteriolar levels which nicely corroborated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…It is apparent that during the earlier phase, the heart attempts to adapt itself against the detrimental effects of angiotensin II by upregulating several cardioprotective genes and proteins. These genes and proteins are redoxregulated and their expressions are blocked by the antioxidants or ROS scavengers [87,88]. An identical pattern of cardioprotective proteins and genes are expressed in the preconditioned heart, which are also inhibited with ROS scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that during the earlier phase, the heart attempts to adapt itself against the detrimental effects of angiotensin II by upregulating several cardioprotective genes and proteins. These genes and proteins are redoxregulated and their expressions are blocked by the antioxidants or ROS scavengers [87,88]. An identical pattern of cardioprotective proteins and genes are expressed in the preconditioned heart, which are also inhibited with ROS scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…It was already reported that activation of MAPK pathway together with inhibition of SAPK/JNK activity by VEGF is the key event in determining whether an endothelial cell is going to survive or will undergo programmed cell death (8). JNK is crucial to programmed cell death induced by TNF receptor, and one mechanism by which NF-B protects cells is downregulation of the JNK cascade through the transcriptional activation of Gadd45␤ (4).…”
Section: Resultsmentioning
confidence: 99%
“…Several observations support the contention that the process of collateral growth is multifactorial. Matsunaga et al (61) observed that vascular endothelial growth factor (VEGF) was , play a key role in many cardiovascular pathologies, such as atherosclerosis and ischemia=reperfusion injury (51,64,67). Moreover, patients with congestive heart failure (CHF) show signs of oxidative stress, and the link between this stress and the progression of CHF is being explored (70).…”
Section: Modelmentioning
confidence: 99%